(untitled) (World Bulletin of Social Sciences, 2023)
The article analyzes the theoretical views on the problem of text units in world linguistics, the study of the paragraph and its occurrence in the text using examples. In particular, paragraphs of free speech were analyzed and highlighted using English-Uzbek literary texts.